Effect of strategic thinking in human resource management strategies “Analytical field study of the views of a sample of managers in the Iraqi Ministry of Health” - الكبيسي, صلاح الدين عواد (Journal of Economics and Administrative Sciences, 2012)
The researcher attempts to diagnose the level of the effect  of strategic thinking skills (intuition, meditation, creativity) of the managers in the Ministry of Health in Iraq and some of its institutions in the formulation of human resources management: (selection, training, incentivence , performance appraisal (Recognizing the importance of the subjects studied, and because of the importance of the expected results of the field under consideration, researcher selected a sample of Size (50) general managers and department managers in the office of the Ministry and the Departments of health Baghdad –Karkh, Rusafa, Medical City and Peoples Clinics, as most interested in the subject the most significant result obtained indiadcated that level of skills of strategic thinking among the headmasters of the field under consideration was above average and a strong reflection to those skills in the strategies of selection ,assignment and less power in the strategy of incentivence and not reflected in the strategies of training and development , performance appraisal.